Preliminary evaluation of FAPI-04-PET/CT for differentiating recurrence and post-treatment changes in high-grade gliomas - Indraja D. Dev; Ameya D. Puranik; Venkatesh Rangarajan; Sukriti Patra; Nilendu Purandare; Arpita Sahu; Amitkumar Choudhary; Kajari Bhattacharya; Tejpal Gupta; Abhishek Chatterjee; Archya Dasgupta; Aliasgar Moiyadi; et al. (Exploration of Targeted Anti-tumor Therapy)
Fibroblast-activated protein (FAP) expression in glial cells is attributed to FAP-positive foci on tumor vessels and neoplastic cells. Preclinical and pilot studies have shown FAP expression in high-grade gliomas. We aimed at comparing PET imaging with FAP-inhibitor (FAPI-PET) with current standard, i.e., fluoro-ethyl tyrosine (FET) PET in post-treatment setting to differentiate recurrence and post-treatment changes. 6 patients with WHO Grade III and IV glioma who received standard treatment underwent Ga-68-FAPI-04 PET/CT (FAPI-PET/CT). Tracer uptake greater than background was considered positive. FET PET was performed and interpreted as per institutional standards, which formed the basis of treatment decision. There was concordance between FAPI expression and FET uptake in 5 patients suggestive of disease recurrence. There was no FAPI expression seen in 1 patient, in whom FET PET was suggestive of post-treatment changes. FAPI PET uptake correlated with amino acid expression to differentiate post treatment changes from recurrence in high-grade glial tumors; further validation with prospective study and histopathological confirmation is needed.